Osmotic stress and recovery in field populations of Zygnema sp. (Zygnematophyceae, Streptophyta) on Svalbard (High Arctic) subjected to natural desiccation - Pichrtová, M. (Martina); Hájek, T. (Tomáš); Elster, J. (Josef) (FEMS Microbiology Ecology, 2014)
All studied populations of Zygnema sp. on Svalbard formed akinetes -- stationary-phase cells filled with storage products. However, the populations differed in their reaction to osmotic stress. Whereas the wet-collected samples were strongly impaired by osmotic stress, the osmotic stress resistance of the naturally dried samples was comparable to that of true aeroterrestrial algae. We showed that arctic populations of Zygnema acclimate well to natural desiccation via hardening that is mediated by slow desiccation. As no other types of specialized cells were observed, we assume that the naturally hardened akinetes also play a key role in winter survival.